Power through: A new concept in the empowerment discourse - Galiè, Alessandra; Farnworth, Cathy Rozel (Elsevier, 2019)
• Current empowerment efforts fail to capture a critical component of empowerment - its relational nature. • Individual's empowerment is constituted through the empowerment of others in significant relationship to them. • The ability of women to empower themselves is mediated through the deliberative support of others. • Community judgment of individual alignment with gender norms determines empowerment outcomes in daily realities. • Public adherence to local gender norms creates a safe façade to deviate from the norms.